PENGARUH LOGISTIC SERVICE QUALITY TERHADAP KEPUASAN KONSUMEN JASA KURIR DI KANTOR POS PALEMBANG - Nourma Wulanda (Jurnal Manajemen Bisnis Unbara, 2022)
This study aims to determine (1) How the impact of timeliness to cunsomer satisfaction at Post Office Palembang, (2) How the impact of accuracy of order to cunsomer satisfaction at Post Office Palembang, (3) How the impact of quality of information to cunsomer satisfaction at Post Office Palembang, and (4) How the impact of quality of contact personnel to cunsomer satisfaction at Post Office Palembang. The study design used is eksplanatory. The samples used were 100 respondens. To measure the influence between variables, used multiple linear regression and to test the hypotheses used to test the hypothesis F and t. Results of the study are: (1) Timeliness have a positive and significant effect to cunsomer satisfaction at Post Office Palembang, (2) Accuracy of order have a positive and significant effect to cunsomer satisfaction at Post Office Palembang, (3) Quality of information have a positive and significant effect to cunsomer satisfaction at Post Office Palembang, and (4) Quality of contact personnel have a positive and significant effect to cunsomer satisfaction at Post Office Palembang.